2017
DOI: 10.1016/j.kint.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Factor H autoantibody is associated with atypical hemolytic uremic syndrome in children in the United Kingdom and Ireland

Abstract: Factor H autoantibodies can impair complement regulation, resulting in atypical hemolytic uremic syndrome, predominantly in childhood. There are no trials investigating treatment, and clinical practice is only informed by retrospective cohort analysis. Here we examined 175 children presenting with atypical hemolytic uremic syndrome in the United Kingdom and Ireland for factor H autoantibodies that included 17 children with titers above the international standard. Of the 17, seven had a concomitant rare genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 52 publications
9
35
1
Order By: Relevance
“…There is a strong association with homozygous deletion of CFHR3 and CFHR1, which encode the proteins FHR3 and FHR1 (21), although the mechanism is not understood; CFHR3/1 deletion is a common polymorphism, and it is not present in all individuals who develop FH autoantibodies (22). It predominantly presents in childhood, frequently with a gastrointestinal prodrome.…”
Section: Acquired Complement-mediated Ahusmentioning
confidence: 99%
“…There is a strong association with homozygous deletion of CFHR3 and CFHR1, which encode the proteins FHR3 and FHR1 (21), although the mechanism is not understood; CFHR3/1 deletion is a common polymorphism, and it is not present in all individuals who develop FH autoantibodies (22). It predominantly presents in childhood, frequently with a gastrointestinal prodrome.…”
Section: Acquired Complement-mediated Ahusmentioning
confidence: 99%
“…The prevalence of antiCFHaHUS shows ethnic differences. However, pre valence in studies reporting exclusively pediatric cases (10-56% of total cases with aHUS) 2,911) is higher than that www.chikd.org in studies reporting both, pediatric and adult cases (5-10 %) 3,11,12) . A large cohort study that included patients with antiCFHaHUS 6) reported that abnormal activation of the alternative complement pathway (low serum C3 levels with normal C4 levels) was observed in 58% of the patients at disease onset, as was observed in our patient.…”
Section: Discussionmentioning
confidence: 79%
“…Patient identification numbers were allocated according to time of referral to our center; they begin at NCL25 to maintain consistency with our previously published study on factor H autoantibody-associated aHUS. 27 Six patients had a renal biopsy (NCL25, NCL26, NCL27, NCL29, NCL34, and NCL37).…”
Section: Patientsmentioning
confidence: 99%